Prediction of single-cross hybrids of maize based on genomic information of the lines (Bioagro, 2024)
The genetic divergence of the parents of a hybrid plays an important role in the expression of heterosis of its progeny. The objective of this research was to predict hybrid combinations using microsatellite-type molecular markers of higher heterotic behavior based on divergence between pairs of lines. Thirty-seven maize lines were genotyped for genetic profiling using microsatellites, with which Rogers' modified genetic distances (GD) were estimated. Forty-six hybrids were generated and evaluated in two locations in Tamaulipas, Mexico, during the autumn-winter 2020 seasons, under a randomized complete block design with three replications. Analysis of variance and linear regression were performed with genetic distances between parent lines as GD versus yield (GRY) and its components as dependent variables. Significance was detected between locations and genotypes for all variables. The superior hybrid in grain yield was LEARB9 × UAY113 with 9.1 t·ha-1. Linear regression analysis revealed a low association, although with significant differences (P≤0.01) between GD vs GRY and cob shelling percentage, with regression coefficients of 4.77 t·ha-1, and 7.13 %, with coefficients of determination R2= 0.14 and 0.06. For GD vs plant height and cob height, a significant (P≤0.01) moderate relationship, regression coefficients of 84.15 and 42.39 cm and coefficients of determination R2 = 0.28 and 0.26. It is concluded that SSRs can be used as tools in traditional hybridization schemes.
Keywords: Genetic distances; hybridization; microsatellites; Zea mays